Impact of cathepsin B-sensitive triggers and hydrophilic linkers on in vitro efficacy of novel site-specific antibody–drug conjugates. Issue 11 (23rd February 2018) - Bryden, Francesca; Martin, Camille; Letast, Stéphanie; Lles, Eva; Viéitez-Villemin, Inmaculada; Rousseau, Anaïs; Colas, Cyril; Brachet-Botineau, Marie; Allard-Vannier, Emilie; Larbouret, Christel; Viaud-Massuard, Marie-Claude; Joubert, Nicolas
Abstract : Promising anti-HER2 site-specific ADCs with an in vitro efficacy equivalent to Kadcyla®. Abstract : Herein we describe the synthesis and evaluation of four novel HER2-targeting, cathepsin B-sensitive antibody–drug conjugates bearing a monomethylauristatin E (MMAE) cytotoxic payload, constructed via the conjugation of cleavable linkers to trastuzumab using a site-specific bioconjugation methodology. These linkers vary by both cleavable trigger motif and hydrophilicity, containing one of two cathepsin B sensitive dipeptides (Val-Cit and Val-Ala), and engendered with either hydrophilic or hydrophobic character via application of a PEG12 spacer. Through evaluation of physical properties, in vitro cytotoxicity, and receptor affinity of the resulting antibody–drug conjugates (ADCs), we have demonstrated that while both dipeptide triggers are effective, the increased hydrophobicity of the Val-Ala pair limits its utility within this type of linker. In addition, while PEGylation augments linker hydrophilicity, this change does not translate to more favourable ADC hydrophilicity or potency. While all described structures demonstrated excellent and similar in vitro cytotoxicity, the ADC with the ValCitPABMMAE linker shows the most promising combination of in vitro potency, structural homogeneity, and hydrophilicity, warranting further evaluation into its therapeutic potential.